Methods for Exodus - Dozeman, Thomas B. (Methods in biblical interpretation, 2010)
Introduction / Thomas B. Dozeman -- Literary and rhetorical criticism / Dennis T. Olson -- Genre criticism / Kenton L. Sparks -- Source and redaction criticism / Suzanne Boorer -- Liberation criticism / Jorge Pixley -- Feminist criticism / Naomi Steinberg -- Postcolonial biblical criticism / Gale A. Yee